1992
DOI: 10.1016/0009-2509(92)87155-j
|View full text |Cite
|
Sign up to set email alerts
|

A catalytically active membrane reactor for fast, exothermic, heterogeneously catalysed reactions

Abstract: ooo9-2509/92 s5.cIo+o.m Printed in Great Britain. 01992FWgMlOIlRessLM A catalytically active membrane reactor for fast, exothemic, heterogeneously catalysed reactions AbstractA membrane reactor with separated feed of reactants is demonstrated as a promising contactor type when dealing with heterogeneously catalysed, very fast and exothermic gas phase reactions. Due to the separation of reactants a good control of the system is obtained, because process variables can be varied independently from each other. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 5 publications
2
47
0
1
Order By: Relevance
“…In earlier papers concerning the operation and the modelling of membrane reactors with separate feed of reactants it was demonstrated that the use of a Stefan-Maxwell approach, particularly in the presence of a pressure difference over the membrane, has to be preferred to a merely Fickian approach [7,8,10]. In this context, the so-called Dusty-Gas Model approach [13] was successfully employed in models based on membrane isothermicity, an assumption supported by the comparatively high membrane conductivity and the limited conversions tested in the above studies.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier papers concerning the operation and the modelling of membrane reactors with separate feed of reactants it was demonstrated that the use of a Stefan-Maxwell approach, particularly in the presence of a pressure difference over the membrane, has to be preferred to a merely Fickian approach [7,8,10]. In this context, the so-called Dusty-Gas Model approach [13] was successfully employed in models based on membrane isothermicity, an assumption supported by the comparatively high membrane conductivity and the limited conversions tested in the above studies.…”
Section: Theorymentioning
confidence: 99%
“…The first studies with this type of reactor were reported in literature by Sloot et al [7] where it was demonstrated, using the Claus reaction as model reaction, that this concept has distinct advantages in the operation of reactions that normally require strict stoichiometric feed rates of reactants. Another application was worked out by Veldsink et al [8] and Saracco et al [9][10][11] for performing fast and exothermic reactions (in their studies: the catalytic combustion of CO and propane, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrically inside the membrane a cooling pipe is placed to remove heat from the membrane surface. A general applicable flux model was developed (Veldsink, 1993), which describes the transport of reactants and products through the membrane accompanied with chemical reactions of arbitrary kinetic rate equations. For a catalytic membrane reactor with separated feed of reactants (CMRSR) slip of unconverted reactants through the membrane substantially reduces the attractive features of this type of reactor.…”
Section: -588519512634-0763$090010mentioning
confidence: 99%
“…Among others, it provides options to improve the reactor control and to avoid the build-up of explosive gas mixtures [2,3]. According to Veldsink et al [ 3 ] slip of unconverted reactants to the opposite side reduces substantially the aforementioned advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, it provides options to improve the reactor control and to avoid the build-up of explosive gas mixtures [2,3]. According to Veldsink et al [ 3 ] slip of unconverted reactants to the opposite side reduces substantially the aforementioned advantages. Therefore, the optimal performance of this type of membrane reactor is obtained for heterogeneous reactions with a high reaction rate compared with the transport rates of reactants through the membrane.…”
Section: Introductionmentioning
confidence: 99%